Governance and Intellectual Capital in Companies that Listed on Indonesia Stock Exchange - Widijaya Widijaya; Elita Elita (Jurnal Akuntansi)
Intellectual capital disclosure uses VAIC (Value-Added Intellectual Coefficient) disclosure methodology that reveals the company's ability to manage its intangible assets over time. The research was conducted using the sampling method from the financial statements of companies listed on the IDX. The financial statements used are reports from 2017 to 2021. The purpose of this study is to show that there is a significant positive, negative, or marginal effect between the variable 'independent committee' and corporate governance represented by board size. The number of committee members, block ownership and committee size indicate the dependent variable measured by the VAIC (Value Added Intellectual Coefficient) method, namely the frequency of intellectual capital examination and audit committee meetings. The validation of this research is done by analysis method using Eviews and SPSS program. The results showed that independent committee, committee size, and audit committee size have an effect on VAIC disclosure, while block ownership and the frequency of audit committee meetings do not.